Pengaruh Profitabilitas, OCF, dan EVA Terhadap Return Saham Perusahaan Manufaktur Yang Terdaftar Di BEI - Marvina Rosa; Erly Mulyani (Universitas Negeri Padang, 2013)
This study aims to examine and discover the extent of empirical evidence:1)the effect of profitability on stock return, 2)Effect of operating cash flow to stock return,3)the effect of economic value added to stock return. This study classified the causative research. The population in this study is manufacturing company listed on the Indonesia Stock Exchange in 2008 until 2010. This study use purposive sampling method and eligible sample much as 52 companies. The analysis used is multiple linear regression and t-test to see the effect of profitability, OCF and EVA to stock return. The test results indicate that:1)profitability had no significant effect positively to stock returns, value of the significance 0,478>α0.05, and β-value 0.083 (H1 rejected).2)operating cash flow had no significant positively to stock returns, value of the significance 0,148>α0.05 and β value -0.150 (H2 rejected).3)economic value added had no significant positively to stock returns, value of the significance 0039<α0.05, but the β-value -0.228(H3 rejected). In this study suggested:1)For investors who want to invest in the stock market, especially in manufacturing companies should also consider other factors such as market sentiment and macro varaibel. 2)For further research can add other variables that might impact on stock returns, such as business risk, market risk, company size, inflation and other macro varaibel. Keywords : ROA, operating cash flow, economic value added, return